2009
DOI: 10.1073/pnas.0901290106
|View full text |Cite
|
Sign up to set email alerts
|

Optical measurement of mGluR1 conformational changes reveals fast activation, slow deactivation, and sensitization

Abstract: Metabotropic glutamate receptor (mGluR) activation has been extensively studied under steady-state conditions. However, at central synapses, mGluRs are exposed to brief submillisecond glutamate transients and may not reach steady-state. The lack of information on the kinetics of mGluR activation impairs accurate predictions of their operation during synaptic transmission. Here, we report experiments designed to investigate mGluR kinetics in real-time. We inserted either CFP or YFP into the second intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 41 publications
(63 reference statements)
4
60
4
Order By: Relevance
“…Indeed, in the proposed resting orientation observed with the soluble VFTs, the CRDs are far apart, as will then be the 7TM domains. However, such proposed conformation of the dimer is not compatible with FRET data obtained when CFP and YFP are fused to the intracellular loops of the receptor (17,36). Indeed these data revealed a close proximity between the 7TM domains, closer that what is expected on the basis of the resting orientation of the VFTs.…”
Section: Discussioncontrasting
confidence: 40%
“…Indeed, in the proposed resting orientation observed with the soluble VFTs, the CRDs are far apart, as will then be the 7TM domains. However, such proposed conformation of the dimer is not compatible with FRET data obtained when CFP and YFP are fused to the intracellular loops of the receptor (17,36). Indeed these data revealed a close proximity between the 7TM domains, closer that what is expected on the basis of the resting orientation of the VFTs.…”
Section: Discussioncontrasting
confidence: 40%
“…Overall, the transitions of GPCRs into truly active conformations appear to be incomplete under physiologic conditions, and stabilization by binding to a G-protein or to a (b-)arrestin appears to be required in order to produce a fully active receptor (Elgeti et al, 2013;Manglik et al, 2015). Activation of nonrhodopsin receptors has been followed mostly using fluorescence resonance energy transfer-based sensors and rapid application of agonists by superfusion; this has led to reported activation times down to 10 milliseconds (Marcaggi et al, 2009), but mostly in the range of 30-80 milliseconds (Vilardaga et al, 2003;Lohse et al, 2008Lohse et al, , 2012. Levitz et al (2013) used a tethered, light-switchable agonist to activate a metabotropic glutamate receptor, but did not determine the speed of activation of the receptor.…”
Section: Temporal Aspects-kinetics Along the Signaling Chainmentioning
confidence: 99%
“…It has been shown that a relative movement at the level of the VFTs, the CRDs (9,20,46), and the 7TMs of the two subunits (19,21,22) occurs during activation of class C GPCRs. More recently, we documented that the change in conformation of one of the 7TM domains within the dimer occurs after the relative movement between the protomers (19), consistent with a concerted activation mechanism that results from dimer rearrangement.…”
Section: Isolated 7tm Reconstituted Into Nanodiscs Retains Its Abilitmentioning
confidence: 99%
“…Structural as well as mutagenesis studies demonstrated a large change in the relative position of the VFTs is associated with dimer activation (9,14,15,20), but this is not consistent with all structures available (8). At the 7TM level, a movement between the two subunits has also been demonstrated using FRET studies (19,21,22). It remains to be determined whether such changes are only associated with the activation process, result as a consequence of other more critical steps, or represent the unique driving force for 7TM activation.…”
mentioning
confidence: 99%